Instagram Usage as Preaching Media (Multimodality Analysis on KH Mustofa Bisri’s Instagram Account @s.kakung) - Laelatul Pathia (Politeknik Negeri Media Kreatif, 2020)
The purpose of this study was to determine the use of Instagram as a media of preaching by KH. Mustofa Bisri or Gus Mus, as well as a visual interpretation of the depth of the da’wah material obtained by users. As a kiai, as well as a humanist, he tries to combine the method of da’wah with the art of exploratory communication, without being patronizing. This study uses a qualitative approach, with data collection techniques and observations of some of Gus Mus’s Instagram followers. The method used in this research is Van Leeuwen’s multimodality analysis. Multimodality refers to the way people communicate using several semiotics of fashion in product design such as visuals, audiovisuals, texts, as well as activities such as engagement on likes, comments, or reposts on Instagram. Multimodality refers to three systems of analysis, namely information value, salience, and framing.